Antioxidant Activity in Melon (Cucumis melo L. 'Gama Melon Parfum') as Antiaging Cream Formulation - Wahyuni, Satria; Wibowo, Wiko Arif; Sulaiman, Teuku Nanda Saifullah; Daryono, Budi Setiadi (Universitas Brawijaya, 2023)
Antiaging cosmetics are becoming increasingly popular among the general public. Melon (Cucumis melo L.) Gama Melon Parfum cultivars ('GMP') are one of the plants that can be utilized as a basic ingredient in the production of antiaging cosmetics. 'GMP' melon has cucurbitacin compounds that can be utilized as antiaging and contains flavonoid, saponin, and terpenoid compounds that have antioxidant properties. This research aims to analyze the difference in antioxidant activity of 'GMP' melon extract and 'GMP' melon cosmetic cream preparation cultivated in Yogyakarta with 'GMP' melon cultivated in Bandung, analyze extract standardization parameters, and determine the phenolic and flavonoid contents of each melon extract contains. The activity of antioxidants was determined by the DPPH method, the Folin-Ciocelteu method to measure phenolics, and the AlCl3 solution-based colorimetric approach to measuring flavonoid content. It was revealed that the highest % RSA of antioxidant activity is in ‘GMP’ melon extract cultivated in Bandung. The results of the standardization of 'GMP' melon extract met the requirements of standard parameters. The greatest total phenolic content is derived from the extract of ‘GMP’ melon in Bandung, while the highest total flavonoid content in 'GMP' melon extracts is cultivated in Yogyakarta. The highest to lowest antioxidant activity of ‘GMP’ melon cream was formula IV (‘GMP’ melon extract 30% cultivated in Bandung), formula III (‘GMP’ melon extract 20% grown in Bandung), formula II (‘GMP’ melon extract 30% cultivated in Yogyakarta), formula I (‘GMP’ melon extract 20% cultivated in Yogyakarta), and the lowest is in K- with formula without ‘GMP’ melon extract.